An ex vivo uterine system captures implantation, embryogenesis, and trophoblast invasion via maternal-embryonic signaling - Takehiro Hiraoka; Shizu Aikawa; Daisuke Mashiko; Tatsuya Nakagawa; Hiroki Shirai; Yasushi Hirota; Hiroshi Kimura; Masahito Ikawa (Nature Communications)
Abstract Embryo implantation remains challenging to study because of its inaccessibility in situ despite its essentiality and clinical significance. Although recent studies on long-term culture of authentic and model embryos have provided significant advances in elucidating embryogenesis in vitro, they, without the uterus, cannot genuinely replicate implantation. Here, we have recapitulated bona fide implantation ex vivo at more than 90% efficiency followed by embryogenesis and trophoblast invasion using authentic mouse embryos and uterine tissue. We utilized air-liquid interface culture method with originally developed devices manufactured with polydimethylsiloxane. Notably, the system replicated the robust induction of a maternal implantation regulator COX-2 at the attachment interface, which was accompanied by trophoblastic AKT activation, suggesting a possible signaling that mediates maternal COX-2 and embryonic AKT1 that accelerates implantation. By expanding the ex vivo findings, embryonic AKT1 transduction ameliorated defective implantation of uterine origin by a COX-2 inhibitor in vivo. The system, proposing a potentially standard platform of embryogenesis, offers a concise, reproducible, and scalable screening system, suggesting significant implications for developmental biology and therapeutic strategies for recurrent implantation failure in assisted reproductive technology.